Primary Droop Current-Sharing Control of the Parallel DC/DC Converters System considering Output Cable Resistance. (6th March 2011) - Wang, J. B.
Abstract : This paper presents a primary droop current-sharing controller that can integrate into voltage feedback controller and, thus, provides a low-cost and simple solution for parallel DC/DC converters system. From the equivalent small-signal model, a two-port network was adapted to describe the output and control variables for designing voltage and droop current-sharing loops. From the analysis results, the designed primary droop current-sharing controller will not affect the original voltage loop gain profile to let the DC/DC converter preserve desire control performance. After designing a stable DC/DC converter with primary droop current-sharing control, the stability of the interconnected parallel DC/DC converters system was studied. When the cable resistance is reduced, when the cable resistance is reduced, the interconnected system might be unstable. Finally, some simulation and experimental results demonstrated the effectiveness of the proposed controller in a prototype parallel DC/DC converters system.